Covid-19 and mutual aid: Prefigurative approaches to caring?. (1st June 2021) - Mayo, Marjorie
Abstract : With over 2, 000 support groups listed in Britain at the time of writing at the beginning of 2021, the growth of mutual aid has been among the more positive outcomes of the Covid-19 pandemic. So much for the neoliberal view of humans as rational individuals focused on the pursuit of their own self-interests, whatever the needs of others. For Marxists, though, the recent growth of mutual aid groups needs to be set within the framework of critical understandings about civil society, the respective roles of civil society, the market and the state, and the potential for building alternatives within capitalist societies. The Covid-19 pandemic has been highlighting the failures of market-led approaches to meeting people's needs, demonstrating the need for more rather than less public provision, including the need for a national care service. Meanwhile, the voluntary and community sectors have been struggling to fill the gaps between shrinking public services on the one hand and growing social needs on the other. This has been the context for the emergence of the mutual aid groups that are the focus of the final section of this article, exploring their potential contributions, promoting values of mutuality, cooperation and care within these contemporary constraints. The article concludes by reflecting on the implications of such prefigurative community-based initiatives more generally, their contributions as well as their inherent limitations as component parts of social justice movements.